2010
DOI: 10.1111/j.1365-2435.2009.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

The leaf economics spectrum and the prediction of photosynthetic light–response curves

Abstract: Summary 1. In this paper we determine whether interspecific variation in entire photosynthetic light–response curves correlates with the leaf traits of the ‘leaf economics spectrum’ (LES) and the degree to which such traits can predict interspecific variation in light–response curves. This question is important because light–response curves are included in many ecosystem models of plant productivity and gas exchange but such models do not take into account interspecific variation in such response curves. 2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 26 publications
4
62
2
1
Order By: Relevance
“…To our knowledge this is the first study attempting to link ecosystem C light response curves to functional diversity indices; we identified predictors whose relevance needs to be further tested in order to extend our understanding from species‐specific light response curves (Marino et al . ) to ecosystem‐level responses. For example, the FDQ‐gs+CWM‐height model predicted best the curvature of the light response curves (θ) (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge this is the first study attempting to link ecosystem C light response curves to functional diversity indices; we identified predictors whose relevance needs to be further tested in order to extend our understanding from species‐specific light response curves (Marino et al . ) to ecosystem‐level responses. For example, the FDQ‐gs+CWM‐height model predicted best the curvature of the light response curves (θ) (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Alongside biomass and LAI effects, we found that the functional diversity indices based on leaf N concentrations (as measured by FD Q -leafN% and FD Q -SLN) are retained as relevant predictors for three of the four parameters (AQY, Rdark and maxNEE) describing the non-rectangular hyperbola function. To our knowledge this is the first study attempting to link ecosystem C light response curves to functional diversity indices; we identified predictors whose relevance needs to be further tested in order to extend our understanding from species-specific light response curves (Marino et al 2010) to ecosystem-level responses. For example, the FDQ-gs+CWM-height model predicted best the curvature of the light response curves (h) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…2005). Within environments, the relationship between SLA and net photosynthesis is robust, but the relationship may be decoupled across environments (Marino et al. 2010; Price & Weitz 2010; Blonder et al.…”
Section: Methodsmentioning
confidence: 99%
“…Given this, it is surprising that so little is known about large scale interspecific covariation between this leaf attribute and other leaf traits. Recent work documenting and quantifying the major axes of variation in leaf functional traits, including some components of gas exchange (photosynthetic rate and stomatal conductance), have ignored variation in stomatal density (D) simply because this variable is rarely studied in an interspecific context (Reich et al 1997;Wright et al 2004;Shipley et al 2006;Marino et al 2010). However, recent comparative work on covariation between D, genome size, and cell size suggests some tantalizing relationships between D and leaf functional traits.…”
Section: Introductionmentioning
confidence: 99%